Toward the benefit and value of immune treatment beyond progression in lung cancer? Insights from a systematic review and meta-analysis - Rui Huangfu; Kun Hou; Jie Zhao; Shikui Wu; Yaodong Ping; Yaodong Ping (Frontiers in Immunology)
ObjectiveImmune treatment beyond progression (ITBP) has emerged as a novel therapeutic strategy in oncology. This systematic review and meta-analysis aim to evaluate the efficacy and safety of ITBP in patients with lung cancer, while also identifying characteristics of populations that may benefit most from this treatment approach.MethodsThis study adheres to the PRISMA guidelines. We searched PubMed, Embase, and the Cochrane Library for relevant literature on immunotherapy for lung cancer, using self-constructed databases up until February 1, 2024. The study includes real-world data from patients with lung cancer undergoing ITBP, categorized into two groups: non-ITBP (NTBP) and ITBP. Two authors independently conducted literature screening, quality assessment, and data extraction. The primary efficacy indicators include overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR). The safety indicator assessed was the incidence of immune-related adverse events (irAEs).ResultsWe included 9 studies with a total of 5,141 patients with lung cancer, comprising 2,051 patients in the ITBP group and 3,090 in the NTBP group. Patients receiving ITBP showed significantly better outcomes than those receiving NTBP, including superior OS and PFS following treatment beyond progression (OS: hazard ratio (HR) 0.72, 95% confidence interval (CI) 0.68-0.77, P < 0.05; PFS: HR 0.63, 95% CI 0.51-0.78, P < 0.05). Additionally, the ITBP group demonstrated higher ORR and DCR (ORR: odds ratio (OR) 0.48, 95% CI 0.31-0.75, P < 0.05; DCR: OR 0.37, 95% CI 0.24-0.57, P < 0.05). No significant difference in the incidence of irAEs was found between the two groups (OR 1.24, 95% CI 0.83-1.85, P > 0.05). Subgroup analysis revealed that factors such as age, gender, lung cancer subtype, and smoking history significantly influenced OS outcomes in the ITBP group.ConclusionOur findings suggest that ITBP is an effective treatment strategy for patients with lung cancer. Further research should focus on identifying specific patient populations that benefit from ITBP and exploring the potential efficacy of combining ITBP with other therapeutic regimens.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024513475.